Second Malignant Neoplasms in Patients With Rhabdomyosarcoma - Hongnan Zhen; Zhikai Liu; Hui Guan; Jiabin Ma; Wenhui Wang; Jing Shen; Zheng Miao; Fuquan Zhang (Frontiers in Oncology, 2021)
ObjectiveRhabdomyosarcoma (RMS) is a rare malignant tumor. The main treatment modality is comprehensive with chemotherapy, radiotherapy, and surgery. With the advancement in recent decades, patient survival has been prolonged, and long-term complications are attracting increasing attention among both physicians and patients. This study aimed to present the survival of patients with RMS and analyze the risk factors for the development of a second malignant neoplasm (SMN).MethodsThe Surveillance, Epidemiology, and End Results (SEER) Program 18 registry database from 1973 to 2015 of the National Cancer Institute of the United States was used for the survival analyses, and the SEER 9 for the SMN analysis.ResultsThe 5-, 10-, and 20-year overall survival rates of the patients with RMS were 45%, 43%, and 33%, respectively. The risk of SMN was significantly higher in patients with RMS compared to the general population (SIR=1.95, 95% CI: 1.44 – 2.57, p < 0.001). The risk of developing SMN was increased in multiple locations, including the bones and joints (SIR = 35.25) soft tissues including the heart (SIR = 22.5), breasts (SIR = 2.10), male genital organs (SIR = 118.14), urinary system (SIR = 2.36), brain (SIR = 9.21), and all nervous system organs (SIR = 8.59). The multivariate analysis indicated that RMS in the limbs and earlier diagnosis time were independent risk factors for the development of SMN. Patients with head and neck (OR = 0.546, 95% CI: 0.313 – 0.952, p = 0.033) and trunk RMS (OR = 0.322, 95% CI: 0.184 – 0.564. p < 0.001) and a later diagnosis time were less likely to develop SMN (OR = 0.496, 95% CI: 0.421 – 0.585, p < 0.001).ConclusionThis study describes the risk factors associated with the development of SMN in patients with RMS, which is helpful for the personalized screening of high-risk patients with RMS.